Blocking Methanation during Reverse Water Gas Shift Reaction on Ni/SiO2 Catalysts by Surface Ag. Issue 3 (5th January 2023) - Zhang, Chu; Zhang, Ruoyu; Liu, Yuxin; Wu, Xiaoxia; Wang, Hua; Ge, Qingfeng; Zhu, Xinli
Abstract: Reverse water gas shift (RWGS) reaction is an attractive approach to convert CO2 with renewable H2 to produce CO. However, this reaction is always accompanied by undesirable methanation reaction lowering the CO selectivity, particularly, at low reaction temperature and on Ni catalysts. Herein, a strategy of deposition of inert Ag on the surface of Ni to block methanation reaction during RWGS for selective conversion of CO2 toward CO was reported. Characterizations showed that in contrast to formation of bulk Ni−Ag alloy, both Ag particle and highly dispersed Ag are direct contacting with Ni particle. Surface Ag modifies the property of Ni geometrically and electronically, resulting in reduced accessible surface Ni sites and Ni ensemble size, as well as electron transfer from Ni to Ag. Consequently, both the amount and strength of CO adsorption are reduced, which facilitates CO desorption and reduces CO methanation activity. The Ag modification tunes Ni/SiO2 from selective methanation to selective RWGS, with 100 % CO selectivity on Ni‐0.3 Ag/SiO2 (Ag/Ni=0.3) at 400 °C with gas hourly space velocity (GHSV) >300 L g −1  h −1 and CO selectivity is >80.7 % even at a low GHSV of 15 L g −1  h −1 . Moreover, the Ni‐0.3 Ag/SiO2 appears to be very stable for RWGS reaction. Abstract : Ni−Ag bimetallic catalyst : Surface Ag modifies the property of Ni geometrically and electronically, resulting in reduced accessible surface Ni sites and Ni ensemble size, as well as electron transfer from Ni to Ag. Consequently, both the amount and strength of CO adsorption are reduced, which facilitates CO desorption and reduces CO methanation activity. The Ag modification tunes Ni/SiO2 from selective methanation to stable selective RWGS.